Treatment of late complications of plombage by simultaneous removal of plomb and decortication. Issue 12 (December 1989) - Moran, A; Stableforth, D E; Matthews, H R
Abstract : Two patients with local complications of plombage were treated by removal of the plomb and decortication at a single operation. This provided immediate re-expansion of the lung and avoided the need for thoracoplasty.